Excessive sedentary time and low cardiorespiratory fitness in European adolescents: the HELENA study. Issue 3 (10th January 2011) - Martinez-Gomez, David; Ortega, Francisco B; Ruiz, Jonatan R; Vicente-Rodriguez, Germán; Veiga, Oscar L; Widhalm, Kurt; Manios, Yannis; Béghin, Laurent; Valtueña, Jara; Kafatos, Anthony; Molnar, Denes; Moreno, Luis A; et al.
Abstract : Background: The aims of this study were to examine what amount of sedentary time is associated with low cardiorespiratory fitness (CRF) in adolescents and whether this association is independent of physical activity. Methods: The study comprised 1808 adolescents aged 12.5–17.5 years from 10 European cities. Sedentary time and moderate-to-vigorous physical activity (MVPA) were measured by accelerometer. CRF was assessed by the 20 m shuttle-run test. Adolescents were divided into two groups (high/low) according to FITNESSGRAM guidelines. Receiver-operating characteristic (ROC) analysis was used to determine thresholds that best discriminate between high and low CRF in adolescents. Results: Adolescent girls had more sedentary time than boys (p<0.001). ROC analysis showed that girls spending ≥69% of waking time in sedentary activities had low CRF, but no significant threshold discriminated between high and low CRF in boys. Adolescent girls who exceeded this threshold had lower levels of CRF (p≤0.001) and were more likely to have a low CRF (OR 1.68, 95% CI 1.22 to 2.31) independent of centre, age and body mass index. The negative influence of excessive sedentary time on CRF remained significant (p=0.045) in adolescent girls who did not meet the physical activity guidelines (<60 min/day in MVPA) but was abolished (p>0.05) in those who met the recommendation (≥60 min/day in MVPA). Conclusion: Excessive sedentary time is associated with low CRF in adolescent girls but not in boys. However, this adverse effect might be attenuated if adolescent girls meet the current physical activity guidelines.